Amount and distribution of 5-methylcytosine in human DNA from different types of tissues of cells. - Ehrlich, M (1982)
Analysis of the total base composition of DNA from seven different normal human tissues and eight different types of homogeneous human cell populations revealed considerable tissue-specific and cell-specific differences in the extent of methylation of cytosine residues. The two most highly methylated DNAs were from thymus and brain with 1.00 and 0.98 mole percent 5-methylcytosine (m5C), respectively. The two least methylated DNAs from in vivo sources were placental DNA and sperm DNA, which had 0.76 and 0.84 mole percent m5C, respectively. The differences between these two groups of samples were significant with p less than 0.01. The m5C content of DNA from six human cell lines or strains ranged from 0.57 to 0.85 mole percent. The major and minor base composition of DNA fractionated by reassociation kinetics was also determined. The distribution of m5C among these fractions showed little or no variation with tissue or cell type with the possible exception of sperm DNA. In each case, nonrepetitive DNA sequences were hypomethylated compared to unfractionated DNA.